(untitled) (PerCursos, 2021)
The purpose of this article is to reflect on the role of the mediators of Jornal Nacional, focusing on the edition of Sergio Moro’s resignation day. We understand by mediators, starting with Gomes (2007), everyone involved in the process of producing and broadcasting journalistic content, such as presenters, reporters, cinematographers and editors. The study was carried out with the support of the theoretical and methodological approach of Addressing Mode.